The Students’ Perception of English as Global Language - Herawati, Irma; Istinganah, Evi Latul (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2024)
Language is a tool for human being to communicate. People deliver the message and express the idea through language. For this time being, English is function as global language. People around the word use this language to communicate with each other. English is used either in economic, political, and also the other activity in the world. In Indonesia, English belongs to the main subject at school. It means that the students must learn the language at the certain level. The research is aimed to know about the students’ perception of English as Global language. The subject of this study is 9 students of ninth grade in one of the state junior high school in Purbalingga. The method of the research was descriptive quantitative research where the researchers used questionnaires to get the data from students. There are sixteen questions which were distributed online by Google Form. The result of the research showed that the students had a good understanding of English either as the language that they have to learn at school or as the global language.